2020
DOI: 10.1187/cbe.19-11-0236
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Psychosocial Interventions to Motivate Instructor Participation in Teaching Professional Development

Abstract: Teaching professional development (TPD) efforts to reform undergraduate education will not meet their goals if instructors are not motivated to attend. Research on psychosocial interventions could be leveraged to design interventions that will increase instructors’ motivation to attend TPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
(287 reference statements)
0
5
0
Order By: Relevance
“…The study examined whether participants understood the concepts of career development and psychosocial support. The findings of the study revealed that most of the participants were able to distinguish between career development and psychosocial support roles of mentors, although some participants were not clear on the meaning of the two concepts (Limeri et al 2020).The findings were similar to those of Hudson (2017) and Matsko et al 2020).This was shown by participants' request for explanation of the concepts of career development and psychosocial support. The majority of them were able to identify career development as the assistance given to the trainee teacher by the mentor during teaching practice in order to accomplish his/her role of teaching the learners.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The study examined whether participants understood the concepts of career development and psychosocial support. The findings of the study revealed that most of the participants were able to distinguish between career development and psychosocial support roles of mentors, although some participants were not clear on the meaning of the two concepts (Limeri et al 2020).The findings were similar to those of Hudson (2017) and Matsko et al 2020).This was shown by participants' request for explanation of the concepts of career development and psychosocial support. The majority of them were able to identify career development as the assistance given to the trainee teacher by the mentor during teaching practice in order to accomplish his/her role of teaching the learners.…”
Section: Discussionmentioning
confidence: 72%
“…Most teacher education programmes include different components like general education, subject matter studies, foundation of education studies, method studies, and field experience-which is commonly known as teaching practice (Chernikova et al 2020). It is through teaching practice that trainee teachers, supported by mentors, experience the normal classroom situation (Dunn and Doolittle 2020;Limeri et al 2020). This paper examines mentors' practices in facilitating career development and providing psychosocial support to trainee teachers during teaching practice.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of research findings, madrasa teachers' gender and teaching duration affect development of professional teaching, but all, teachers in all four experience groups have positive possibilities [15], [45]- [48]. An important part of the literature considers the skill of professional teaching, which has long been very useful if only because of its positive influence on understanding of madrasa professional teaching materials.…”
Section: Discussionmentioning
confidence: 94%
“…Regardless of the research findings, the merger of madrasah teacher teaching time developing of professional teaching and, above all, teachers who certified less than 5 years, 5-10 years and teachers who certified above 10 years, have positive possibilities (Jurkowski & Müller, 2018;Limeri et al, 2020;Grise-Owens et al, 2018;Alt, 2018). An important part of the literature considers the skill of the developing of teacher professional teaching which has long been very useful teaching, if only because of its positive influence on the understanding of madrasah teacher professional teaching materials.…”
Section: E Discussionmentioning
confidence: 96%